Precoded and vector OFDM robust to channel spectral nulls and with reduced cyclic prefix length in single transmit antenna systems. - Xiang-Gen Xia (IEEE Transactions on communications)
The performance of orthogonal frequency-division multiplexing (OFDM) systems may be degraded when intersymbol interference (ISI) channels have spectral nulls. Also, when ISI channels have many taps, the data rate overhead due to the insertion of the cyclic prefix is high. We first propose a precoded OFDM system that may improve the performance of the OFDM systems for spectral null channels. We also propose size K×x1 vector OFDM (VOFDM) systems that reduce the cyclic prefix length by K times compared to the conventional OFDM systems. The precoding scheme is simply to insert one or more zeros between each two sets of K consecutive information symbols, although it can be generalized to a general form. This precoding scheme may be able to remove the spectral nulls of an ISI channel without knowing the ISI channel. When no zero is inserted between each two sets of K consecutive information symbols and only each K consecutive symbols are blocked together, we obtain VOFDM systems. Both theoretical performance analysis and simulation results are presented. Finally, we compare the combination of the VOFDM systems and the unitary matrix modulation with the conventional OFDM systems and the phase-shift keying modulation, where both differential (noncoherent) and coherent modulations and demodulations are considered